Effects of experimenting with physical and virtual manipulatives on students' conceptual understanding in heat and temperature - Zacharia, Zacharias C.; Papaevripidou, Marios; Olympiou, Georgios (My University, 2008)
This study aimed to investigate the comparative value of experimenting with physical manipulatives (PM) in a sequential combination with virtual manipulatives (VM), with the use of PM preceding the use of VM, and of experimenting with PM alone, with respect to changes in students' conceptual understanding in the domain of heat and temperature. A pre-post-comparison study design was used which involved 62 undergraduate students that attended an introductory course in physics. The participants were randomly assigned to one experimental and one control group. Both groups used the same inquiry-oriented curriculum materials. Participants in the control group used PM to conduct the experiments, whereas, participants in the experimental group used first PM and then VM. VM differed from PM in that it could provide the possibility of faster manipulation, whereas, it retained any other features and interactions of the study's subject domain identical to the PM condition. Conceptual tests were administered to assess students' understanding before, during, and after the study's treatments. Results indicated that experimenting with the combination of PM and VM enhanced students' conceptual understanding more than experimenting with PM alone. The use of VM was identified as the cause of this differentiation.
Keywords: Physics; Students; Permanent magnets; Differentiation (Cognition)